Impact of the surplus distribution principle on the development of agricultural cooperatives in China - Yugang Han; Yating Nie; Aihua Lv; Lei Ye (PLoS ONE, 2025)
Surplus distribution is at the core of cooperative systems. This study examines the impact of the surplus distribution principle on the development of agricultural cooperatives. We utilize panel data on cooperative development and surplus distribution for 30 provinces in China from 2008 to 2021 to identify the development pattern and surplus distribution status of cooperatives. A two-way fixed effects model is used as a benchmark to examine the impact of the surplus distribution principle on the development of cooperatives. The empirical analysis shows that the surplus distribution method, which strictly adheres to a trading return of more than 60% of the distributable surplus, has a significant negative impact on cooperative membership size but a significant positive impact on cooperative income. These results remain robust after controlling for the estimation method, replacing the core explanatory variables, shrinking the tails, and conducting endogeneity tests. This study contributes to a macro-level understanding of the impact of the surplus distribution principle on the performance and scale of cooperatives and provides important policy insights for promoting surplus distribution standardization in farmers’ cooperatives and guiding members to establish a stable benefit-linkage mechanism within cooperatives.